Effect of returning home on university student hunger during South African COVID-19 lockdown - Fezile Wagner; Unathi Kolanisi; Ryan G. Wagner; Lerato P. Makuapane; Mxolisi Masango; Francesc Xavier Gómez-Olivé (PLoS ONE, 2026)
The COVID-19 pandemic exacerbated hunger levels in South Africa, with an increase from 10% pre-pandemic to 23% during the pandemic. Pre-pandemic national and global research identified university students to be more vulnerable to hunger compared to the general population. This elevated risk is commonly associated with prevalent financial mismanagement in this group. However, research investigating the prevalence of hunger during the pandemic among this at-risk group is limited. This cross-sectional study aimed to assess the prevalence and determinants of hunger among students at a South African university during the COVID-19 lockdown, with particular focus on the effect of returning home. An online, self-administered survey produced a sample of 596 students. The Household Hunger Scale (HHS) was used to assess hunger. Most students (84%) who resided in on- or off-campus residences before the lockdown returned home during the lockdown. The weighted prevalence of hunger during lockdown was 16.4% (95%CI 13.6%, 19.6%). Bivariate analyses found living alone to be significantly associated with hunger, while multivariate analyses found that first-generation students (adjusted odds ratio (aOR) = 1.78; 95%CI: 1.04, 3.07, p = 0.015), financial aid recipients (aOR = 2.69; 95%CI: 1.47, 4.91, p = 0.001), and those experiencing financial stress/worry (aOR = 3.38; 95%CI: 1.85, 6.18, p < 0.001) were significantly more likely to experience hunger. The high prevalence of hunger during lockdown is concerning, the mandated return of students to their homes during the pandemic may have been a mitigating factor. Profiling students at risk for hunger may allow support services to implement targeted interventions when confronted with similar circumstances in future.